Robotic Assisted Upper Limb Training Post Stroke: A Randomized Control Trial Using Combinatory Approach Toward Reducing Workforce Demands - Budhota, Aamani; Chua, Karen S. G.; Hussain, Asif; Kager, Simone; Cherpin, Adèle; Contu, Sara; Vishwanath, Deshmukh; Kuah, Christopher W. K.; Ng, Chwee Yin; Yam, Lester H. L.; Loh, Yong Joo; Rajeswaran, Deshan Kumar; et al. (Frontiers in Neurology, 2021)
Post stroke upper limb rehabilitation is a challenging problem with poor outcomes as 40% of survivors have functionally useless upper limbs. Robot-aided therapy (RAT) is a potential method to alleviate the effort of intensive, task-specific, repetitive upper limb exercises for both patients and therapists. The present study aims to investigate how a time matched combinatory training scheme that incorporates conventional and RAT, using H-Man, compares with conventional training. In a randomized control trial (NCT02188628, www.clinicaltrials.gov), 44 subacute to chronic stroke survivors with first-ever clinical stroke and predominant arm motor function deficits were recruited and randomized into two groups of 22 subjects: Robotic Therapy (RT) and Conventional Therapy (CT). Both groups received 18 sessions of 90 minutes; three sessions per week over six weeks. In each session, participants of the CT group received 90 minutes of conventional therapy while participants of the RT group underwent combinatory training which consisted of 60 minutes of H-Man therapy followed by 30 minutes of conventional therapy. The clinical outcomes (Fugl-Meyer (FMA), Action Research Arm Test and, Grip Strength) and the quantitative measures (smoothness, time efficiency, and task error, derived from two robotic assessment tasks) were independently evaluated prior to therapy intervention (week 0), at mid-training (week 3), at the end of training (week 6) and post therapy (week 12 and 24). Significant differences within group were observed at the end of training for all clinical scales compared with baseline (mean and standard deviation of FMA score changes between baseline and week 6; RT: Δ4.41 (3.46) and CT: Δ3.0 (4.0); p < 0.01). FMA gains were retained 18 weeks post-training (week 24; RT: Δ5.38 (4.67) and week 24 CT: Δ4.50 (5.35); p < 0.01). The RT group clinical scores improved similarly when compared to CT group with no significant inter-group at all time points although the conventional therapy time was reduced to one third in RT group. There were no training-related adverse side effects. In conclusion, time matched combinatory training incorporating H-Man RAT produced similar outcomes compared to conventional therapy alone. Hence, this study supports a combinatory approach to improve motor function in post-stroke arm paresis.